Superficial morphology and mechanical properties of in vivo aged orthodontic ligatures - Glaucio Serra Guimarães; Liliane Siqueira de Morais; Margareth Maria Gomes de Souza; Carlos Nelson Elias (Dental Press Journal of Orthodontics, 2013)
INTRODUCTION: The degradation of elastic ligatures in the oral environment results in the need of periodic replacement to maintain the optimal force during the orthodontic treatment. The purpose of this study was to perform a clinical prospective randomized study of the degradation of orthodontic elastomeric ligatures in the oral environment by scanning electron microscopy (SEM) and tensile strength test. METHOD: Two hundred elastic ligatures were randomly selected and placed around the brackets of 5 volunteers and removed in groups of 10, at different times (1, 2, 3, and 4 weeks). The control group was performed by another fifty ligatures which were not submitted to the oral degradation. The analyses were done by scanning electron microscopy (SEM) and strength mechanical test. RESULTS: The tensile strength test results showed reduction in the ultimate strength values after four weeks ageing in the oral environment and no statistical difference in the yield strength values (p < 0.05). The orthodontic elastomeric ligatures surface was significantly degraded in the oral cavity after four weeks. The elastomeric degradation began in the first week when the increase in the roughness could be detected just in some areas. Afterwards, the surface became gradually rougher and, after 4 weeks, it was totally rough with some crack areas. CONCLUSIONS: The elastic ligatures aged in the oral environment showed higher superficial degradation and lower loss of mechanical properties after the maximum experimental period.